Certificateless and provably-secure digital signature scheme based on elliptic curve - Dhanashree Toradmalle; Jayabhaskar Muthukuru; B Sathyanarayana (Institute of Advanced Engineering and Science, 2019)
With the internet today available at the user’s beck, and call data or Information Security plays a vital role. Confidentiality, Integrity, Availability, and Non-repudiation are the pillars of security on which every application on the web is based on. With these basic requirements the users also need the security in low resource constrained environments making it more challenging for the security experts to design secured cryptographic algorithms. Digital Signatures play a pivotal role in Authentication. They help in verifying the integrity of the data being exchanged. Elliptical curves are the strongest contenders in Digital Signatures, and much research is being done to enhance the method in many ways. The paper briefs a secured and improved ECDSA Elliptical Curve Digital Signature Algorithm which is an improved and secured version of the Digital Signature Algorithm.